2021
DOI: 10.30892/gtg.35210-656
|View full text |Cite
|
Sign up to set email alerts
|

Developing Smart Tourism Using Virtual Reality as a Tourism Promotion Strategy in Indonesia

Abstract: Technological developments have forced several sectors to adapt to technology, one of which is the tourism sector. Departing from the need for effective and efficient promotional tools in the development and marketing strategies of potential tourism destinations in Indonesia, this study aims to develop a tourism information system (SIPADU) with the concept of mtourism based on android using virtual reality technology. The research and development (R&D) was used as a research method by applying ADDIE model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
0
17
0
3
Order By: Relevance
“…Another cluster establishes the relationship of management with smart tourism and technological adoption. In this cluster, advances are found in developing tourism information systems based on Android and virtual reality technology for tourism promotion (Idris et al, 2021). In addition, the development of smart tourism applications aims to present sites of interest to tourists with ratings, reviews, prices, and current data (Demir et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another cluster establishes the relationship of management with smart tourism and technological adoption. In this cluster, advances are found in developing tourism information systems based on Android and virtual reality technology for tourism promotion (Idris et al, 2021). In addition, the development of smart tourism applications aims to present sites of interest to tourists with ratings, reviews, prices, and current data (Demir et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These studies were more dispersed regarding their focus of analysis. Specifically, topics were found related to gamification and accessible tourism (e.g., Huang and Lau 2020 ), smart and sustainable tourism systems (e.g., Lim et al 2017 ; Moustaka et al 2019 ), value co-creation and smart service ecosystem (e.g., Polese et al 2018 ), promotional strategies (e.g., Idris et al 2021 ), and smart tourism sustainability (e.g., Gomis-López and González-Reverté 2020 ; González-Reverté 2019 ; Križaj et al 2021 ; Zeng et al 2020 ). Questionnaires and interviews (e.g., Gomez-Oliva et al 2019 ; Liu et al 2019 ), interviews and secondary data provided by business analytics (e.g., Del Vecchio et al 2018 ; Del Vecchio et al 2022 ), or questionnaires and focus groups (e.g., Ramos-Soler et al 2019 ) were the most observed methods among mixed methods approaches.…”
Section: Methodsmentioning
confidence: 99%
“…These potentialities offer new management model opportunities (Ivars-Baidal et al 2019 ; Zubiaga et al 2019 ), where technology and data are central actors (Ivars-Baidal et al 2019 ). The main applications of smart technology in this field concern spatial distribution and monitoring visitors’ flows (Crivellari and Beinat 2020 ; Del Vecchio et al 2018 ; Encalada et al 2017 ; Kim et al 2019 ; Zubiaga et al 2019 ), sustainable tourism (Saltos et al 2021 ; Vizuete et al 2021 ), tourism promotion (Idris et al 2021 ), and heritage preservation (Slavec et al 2021 ).…”
Section: Content Analysismentioning
confidence: 99%
“…It is a thinking concept and design method that runs through the entire product design process from the overall situation. Digital design should not be simply used as a drawing or performance tool [22]. Under the conditions of digital technology, different design software will be applied to different stages of product development, and the development of design ideas and the methods and processes used in design will show a new look.…”
Section: Product Design and Development Process In Digitalmentioning
confidence: 99%